2023
DOI: 10.1038/s41419-023-05830-z
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell sequencing reveals homogeneity and heterogeneity of the cytopathological mechanisms in different etiology-induced AKI

Abstract: Homogeneity and heterogeneity of the cytopathological mechanisms in different etiology-induced acute kidney injury (AKI) are poorly understood. Here, we performed single-cell sequencing (scRNA) on mouse kidneys with five common AKI etiologies (CP-Cisplatin, IRI-Ischemia-reperfusion injury, UUO-Unilateral ureteral obstruction, FA-Folic acid, and SO-Sodium oxalate). We constructed a potent multi-model AKI scRNA atlas containing 20 celltypes with 80,689 high-quality cells. The data suggest that compared to IRI an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…Due to the significant increase in ferroptosis levels in IR and the subsequent increase observed in UUO, as shown in the study by Zhimin Chen et al, 20 we established mouse models for both IR and UUO at 1 day, 7 days, and 14 days. In IR, we noted a gradual worsening of renal injury and fibrosis over time, along with a significant increase for ACSL4 as early as IR D1 ( Supplementary Figure S3A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the significant increase in ferroptosis levels in IR and the subsequent increase observed in UUO, as shown in the study by Zhimin Chen et al, 20 we established mouse models for both IR and UUO at 1 day, 7 days, and 14 days. In IR, we noted a gradual worsening of renal injury and fibrosis over time, along with a significant increase for ACSL4 as early as IR D1 ( Supplementary Figure S3A ).…”
Section: Resultsmentioning
confidence: 99%
“…18 Bone marrow mesenchymal stem cells that overexpress GCLC was found to alleviate acute lung injury through anti-apoptotic effects. 19 In this study, the transcriptional characteristics of distal renal tubules in various AKI models were analyzed using scRNA-seq data from Zhimin Chen et al 20 The marker Gclc of the distal renal tubule was identified through scRNA-seq and renal transcriptomics data. Furthermore, the role of Gclc in acute kidney injury was explored by targeting Gclc.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports suggest that ferroptosis may promote cellular susceptibility to apoptosis, and the damaged mitochondria and lipid peroxide from ferroptosis would initiate and drive apoptotic signals [ 37 , 49 ]. Single cell sequencing demonstrated that both ferroptotic and apoptotic proteins could be changed simultaneously in the same cells [ 50 ]. This evidence points to the complexity of cell fate under different disease conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in the UUO model there is no tubular recovery, so it is not an ideal model to study tubular injury and repair. Also, the precise cytopathological mechanisms driving UUO-induced renal injury are poorly understood ( 35 ). In addition, fibrosis develops very rapidly in the model, which limits the experimental window for testing potential ameliorating interventions unless they are introduced before the UUO injury or are expected to have profound effects ( 36 , 37 ).…”
Section: Experimental Models Of Ureteral Obstructionmentioning
confidence: 99%